The Regular Domination Number of Some Special Graphs - Rani, Jyoti; Mehra, Seema (Communications in Mathematics and Applications, 2024)
The purpose of this article is to illustrate the concept of regular domination on a variety of unique graph types, including complete graphs, path graphs, cycle graphs, lollipop graphs, barbell graphs, gear graphs, Petersen graphs, helm graphs, jellyfish graphs, jewel graphs, and complete bipartite graphs. We also determine the regular domination for specific operations, such as the join of two graphs and the corona product of two graphs.